A Europium-based MOF Fluorescent Probe for Efficiently Detecting Malachite Green and Uric Acid - Han, Li-Juan; Kong, Ya-Jie; Hou, Guo-Zheng; Chen, Hua-Chong; Zhang, Xing-Min; Zheng, He-Gen (Inorganic chemistry, 2020)
Lanthanide (such as Tb and Eu) metal–organic frameworks (MOFs) have been widely used in fluorescent probes because of their multiple coordination modes and brilliant fluorescence characteristic. Many lanthanide MOFs were applied in detecting metal ions, inorganic anions, and small molecules. However, it’s rarely reported that Ln-MOF was devoted to detecting malachite green (MG) and uric acid (UA). We prepared a europium-based metal–organic framework (Eu-TDA) (TDA = 2,5-thiophenedicarboxylic acid group). Luminescence studies demonstrated that Eu-TDA can rapidly detect MG and UA with excellent selectivity and sensitivity, where individual quenching efficiency K sv (MG: 5.8 × 105 M–1; UA: 4.15 × 104 M–1) and detection limit (MG: 0.0221 μM; UA: 0.689 μM) were regarded as the excellent MOF sensors for detecting MG and UA. The quenching of Eu-TDA’s fluorescence emission by MG and UA was likely due to the spectral overlap, energy transfer, and competition. Among 11 metal cations and 14 anions, Eu-TDA can quickly and effectively recognize MG and UA with highly selective and sensitive properties. Our method possesses potential application in detecting UA in human blood and MG in the fishpond.